Prevalence of enterotoxins and other virulence genes of Staphylococcus aureus caused subclinical mastitis in dairy cows - Ewida, Rania M. (Vet World, 2020)
BACKGROUND AND AIM: Milk production is one of the main props for the national economy. One of the crucial problems in this industry is subclinical mastitis, which harms this industry that considered the backbone of the economy. It is an infectious and zoonotic disease; the infection can spread between dairy animals through milkers’ hands, and milking machines, while the human infection occurs due to the consumption of apparently hygienic milk. Staphylococcus aureus is one of the main causative agents of clinical and subclinical mastitis. It is also considered one of the bacteria incriminated in food intoxication of humans due to its virulence factors as enterotoxins and toxic shock syndrome. The current study was designed to assess the prevalence of S. aureus and its enterotoxins, as well as, its other virulence factors in milk collected from cows that suffer from subclinical mastitis. MATERIALS AND METHODS: Sixty cows were collected from different dairy farms located in Assiut Governorate, Egypt. These cows were subjected to the clinical examination of the udder and its lymph nodes before sampling. Milk samples were collected from clinically healthy udders. All the milk samples were examined by California mastitis test (CMT), polymerase chain reaction (PCR), and enzyme-linked immunosorbent assay (ELISA) for confirmation subclinical mastitis, presence of S. aureus and its enterotoxins genes and other virulence factors in the examined milk samples. RESULTS: The cows included in the current study had healthy udders. The sixty collected milk samples were tested by CMT. 48/60 (80.0%) were positive samples; from the 48 positive samples, 46 (95.83%) samples were confirmed positive by S. aureus 16s rRNA PCR assay. Multiplex PCRs confirmed the presence of staphylococcus enterotoxin gene C (sec) in one sample, staphylococcus enterotoxin gene D (sed) in 23 samples, while ELISA assay confirmed the presence of the same enterotoxin in only two samples. On the other hand, other groups of genes responsible for some other virulence factors of S. aureus like the extracellular thermostable nuclease (nuc) gene were found in 33 samples, while toxic shock syndrome (tsst) gene and methicillin restraint S. aureus (mecA) gene were not detected in this study. CONCLUSION: Subclinical mastitis is one of the hidden factors that adversely affect the health of both animals and humans. The milk is usually appeared good and may be consumed by humans especially children; however, it causes severe public health problems. In addition, the infected animals with this form of mastitis can spread the infection to other dairy animals and may be turned to a clinical case of contagious mastitis that may be ended by animal culling or death. S. aureus is one of the main causes of subclinical mastitis in cattle. In addition to extracellular thermostable nuclease (nuc) gene, staphylococcus enterotoxin gene C (sec) and staphylococcus enterotoxin gene D (sed) are the most common virulence genes confirmed in subclinical mastitis milk. These results highlighted the need to apply more hygienic measures in the dairy farms to avoid spreading the infection between animals to ensure the production of safe and healthy food to humans.